Optimalisasi Pembelajaran Bilingual Preview-Review sebagai Wahana untuk Melatih Pemahaman Konsep dan Speaking Ability Mahasiswa S1 Pendidikan IPA Undiksha - luh mitha priyanka (Wahana Matematika dan Sains: Jurnal Matematika, Sains, dan Pembelajarannya, 2021)
This study aims to reveal the effectiveness of preview-review bilingual instructional model on the conceptual understanding and speaking ability undergraduate student of science education. This study is quasy experiment with post-test only control group design. Subject of this study are undergraduate student of science education class 1A who join conventional bilingual instructional model and undergraduate student of science education class 1B who join preview-review bilingual instructional model. Data were collected through tests to determine the understanding of students 'concepts and non-test through observation sheets to measure students' speaking abilities. Data was analyzed using prerequisite tests and hypothesis testing. The prerequisite test was carried out with the normality test, homogeneity, variance-covariance matrices, and correlation between dependent variables, while the hypothesis test was carried out by using the Manova test with 5% of significance level. The results of data analysis show that there are differences in concept understanding and speaking ability between Science Education students who join preview-review bilingual instructional model and conventional bilingual instructional model in Basic Science courses.